(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article highlights the importance of digital educational technologies in the lifelong learning of teachers in the vocational education system, as well as the use of educational platforms and Internet resources in the educational process, the possibility of using modern forms of digital technologies in teaching